Citizenship Education in Nigeria as an Alternative to National Unity - OSSAI, Anthony Great (JIE (Journal of Islamic Education), 2023)
Nigeria, as a multicultural society, is confronted with issues of ethnicity, insecurity, corruption, political crises, ethnoreligious dichotomies, weak institutions, and poor governance, which result in a lack of trust among its citizens. As a result, many Nigerians advocate secession, while others advocate restructuring. This research aims to explain the place of citizenship education in Nigeria's national unity process. They are using qualitative methods with an interpretive paradigm approach. Civic education produces active citizens who are socially responsible, sensitive, adaptable, and socially intelligent members of their immediate environment and broader society. Genuine national unity will be ushered in by a sincere and willful commitment among Nigeria's diverse citizens to live honestly and consistently, demonstrated in a progressive nation working towards long-term development for present and future generations. This research suggests a way forward to include, among other things, that all Nigerian citizens should seek to imbibe the spirit of accommodating and working with others to promote national unity and integration.